Pengaruh Fasilitas Peralatan Praktik terhadap Hasil Keterampilan Pengelasan Siswa Kelas XI Jurusan Teknik Pengelasan dan Fabrikasi Logam di SMK Negeri 2 Payakumbuh. - Abdilah, Zikri; Irzal, Irzal; Afnison, Wanda; Alfana, Yogi Dian (TSAQOFAH, 2026)
Welding is one of the essential competencies that students in the Welding and Metal Fabrication Engineering Expertise Program must possess. However, the practical learning process still faces limitations in equipment facilities, both in terms of quantity and usability, requiring students to take turns using the equipment and making practice time less effective. This condition has the potential to affect students’ welding skill outcomes. This study aims to determine the effect of practical equipment facilities on the welding skill outcomes of Grade XI students in the Welding and Metal Fabrication Engineering Department at SMK Negeri 2 Payakumbuh. This study employed a quantitative approach with a correlational method. The research population included all Grade XI students in the Welding and Metal Fabrication Engineering Department of SMK Negeri 2 Payakumbuh, totaling 55 students. The sample was determined using the total sampling technique, so the entire population was used as the research sample. Data were collected through a questionnaire to measure practical equipment facilities and an assessment rubric to measure students’ welding skills. Data analysis included prerequisite analysis tests, namely normality, linearity, and homoscedasticity tests, as well as hypothesis testing using simple linear regression, the t-test, and the coefficient of determination (R²). The results show that practical equipment facilities do not have a significant effect on students’ welding skill outcomes, with a significance value of 0.318 > 0.05. The coefficient of determination (R²) value of 0.019 indicates that practical equipment facilities can explain only 1.9% of the variation in students’ welding skill outcomes, while 98.1% is influenced by other factors outside this study. In addition, the direction of the relationship obtained is negative and not significant, with a regression coefficient value of -0.187. The conclusion of this study emphasizes that practical equipment facilities are not the main factor determining students’ welding skills; rather, other factors play a greater role, such as interest, motivation, theoretical understanding, and the learning process. The implications of this study emphasize the importance of a more comprehensive evaluation of practical learning by considering students’ internal factors and the quality of the vocational learning process.